Evaluation in vitro of the cytotoxicity and genotoxicity of silica nanoparticle aggregates synthesized by the sol-gel method (2015)
Amorphous silica nanoparticles (NPs) has become attractive for biomedical applications. In the present study, the toxicity of different concentrations of amorphous silica NPs of 27 nm was evaluated, such NPs synthesized by. the sol-gel method assisted by